Aggregation of mummified adult crabeater seals (Pinnipedia: Phocidae) in the eastern Antarctic Peninsula: age and sex structure, taphonomy and cause of death - Negrete, Javier; Soibelzon, Leopoldo Héctor; Soibelzon, Esteban; Márquez, Maria E. I.; Loza, Cleopatra Mara; Acosta, Walter; Lusky, Jorge; Pecoraro, Marcelo Ricardo (Antarctic Science)
In Antarctica, crabeater seals tend to strand as immature animals with disorientation, due to their inexperience, given as the probable cause. In 2012 and 2013, we examined a group of 80 mummified crabeater seals on Seymour Island (Marambio). The age and gender of 28 seals was determined, and virology and stomach content analyses were performed in order to determine the cause of stranding. Around 82% of the seals examined were adults and 79% were females, some of which were pregnant. All of the seals sampled tested negative for Morbillivirus, suggesting that the stranding was not related to the mass mortality event reported in the 1950s in the region. Most seals had empty stomachs and thin blubber suggesting that they died from starvation. The state of the carcasses suggests multiple stranding events. Most of the seals were located along an ice-covered stream, suggesting that this may act as a ‘natural trap’, isolating the seals from the open ocean. This is exceptional as it is the first report of mostly adult female seals to strand in Antarctica and refutes the theory that only young animals are prone to stranding. Fil: Negrete, Javier. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Soibelzon, Leopoldo Héctor. Universidad Nacional de la Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Soibelzon, Esteban. Universidad Nacional de la Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Márquez, Maria E. I. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Loza, Cleopatra Mara. Universidad Nacional de la Plata. ...